Mecanismos neuroinflamatórios in vitro do alumínio em células microgliais: envolvimento da via de sinalização purinérgica - Assmann, Charles Elias (2021)
Aluminum is a toxic metal to the nervous tissue and an etiological factor of neurodegenerative diseases, particularly Alzheimer's disease (AD). Furthermore, microglial cells and cellular signaling pathways, such as the purinergic system, are involved in neuroinflammation and neurodegeneration. However, aluminum effects and the participation of the purinergic system in the responses induced by this metal in microglial cells are poorly understood. Thus, the mechanisms associated with the neuroinflammatory profile of aluminum and the involvement of purinergic system components were investigated. The work was carried out, in vitro, with protocols exposing microglial cells to aluminum, in the form of aluminum chloride (AlCl3). The BV-2 cell line, commercially acquired, was grown under standard conditions. The AlCl3 concentration curve (1, 5, 10, 50, 100, 500 and 1000 μM) was used at different exposure times (6, 24 and 96 hours). Lipopolysaccharide (LPS, 1 μg/mL) was used as a pro-inflammatory control. The control group was not exposed to treatments. The uptake of aluminum, activities of the purinergic enzymes nucleoside triphosphate diphosphohydrolase (NTPDase) (substrates adenosine triphosphate (ATP) and adenosine diphosphate (ADP)), 5’-nucleotidase (5'-NT) (substrate adenosine monophosphate (AMP)) and adenosine deaminase (ADA) (substrate adenosine) and expression/protein levels of purinoreceptors (P2X7, A1 and A2A) were evaluated. Besides, cell viability/proliferation, propidium iodide (PI) uptake, oxidative stress parameters (reactive species, superoxide anion, nitric oxide), apoptosis, cell cycle regulation, genotoxicity, expression (NLRP3 inflammasome, interleukins IL-β, IL-6 and IL-10, interferon gamma (IFN-γ), and tumor necrosis factor alpha (TNF-α)) and protein density (NLRP3, nuclear factor kappa B (NF-ƙB), IL-β, and TNF-α) of inflammatory mediators were investigated. Initially, the presence of aluminum in microglial cells was verified. LPS reduced nucleotide hydrolysis (ATP, ADP and AMP), an effect also observed for AlCl3; AlCl3 500 and 1000 μM reduced the hydrolysis of ATP and AMP and AlCl3 1000 μM decreased the hydrolysis of ADP. For ADA, LPS and AlCl3 (500 and 1000 μM) increased adenosine hydrolysis. For purinoreceptors, LPS and AlCl3 1000 μM increased protein levels/expression of P2X7 and A2A, and decreased A1 expression/density. Moreover, AlCl3 decreased cell viability and proliferation, results supported by the increased incorporation of intracellular PI. For oxidative stress, AlCl3 increased levels of nitric oxide, superoxide anion (500 and 1000 μM) and reactive species (100, 500 and 1000 μM), also showing genotoxic potential, increasing DNA damage (500 and 1000 μM, Alkaline Comet assay) and double-stranded DNA (dsDNA) levels (1000 μM). Furthermore, AlCl3 increased the number of cells in the early stages of apoptosis (100, 500 and 1000 μM) and in late apoptosis or already dead (1-1000 μM) and decreased the number of cells in the S and G2/M phases (50-1000 μM) of the cell cycle. For the expression of inflammatory markers, LPS and AlCl3 1000 μM increased mediators such as NLRP3, TNF-α, IFN-γ and IL-1β; on the other hand, for protein density, LPS and AlCl3 1000 μM increased the levels of IL-1β and TNF-α. Thus, the compilation of results suggests that aluminum triggers oxidative-inflammatory responses in microglial cells, possibly involving components of the purinergic signaling pathway.